2020
DOI: 10.3390/app10010422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzoxazine-Based N-Doped Mesoporous Carbons as High-Performance Electrode Materials

Abstract: In this work, nitrogen-doped carbon materials (NCMs) were prepared using aniline-phenol benzoxazine (BOZ) or aniline-cardanol benzoxazine as the carbon precursor and SBA-15 as the hard template. The effects of the carbonization temperature (700, 800, and 900 °C) and different nitrogen contents on the electrochemical properties of carbon materials were investigated. The samples synthesized using aniline-phenol benzoxazine as precursors and treated at 900 °C (NCM-900) exhibited an excellent electrochemical perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Similarly, Zhang et al observed similar properties in nitrogen doped benzoxazines (prepared as shown in Figure 9), finding that the sample with a lower nitrogen content had both a larger specific surface area and larger pore volumes than others [57]. Pores with higher surface areas have an increased ability to accumulate charges and transport ions, thus porosity measurements are crucial to understanding the electrochemical properties of benzoxazines [56,57]. Aside from porosity in general, mesopores can create ion transport channels within the carbon material (and grant ions entry to the electrode), thus highly mesoporous benzoxazines are highly suitable as electrodes [56].…”
Section: Electrochemical Propertiessupporting
confidence: 53%
See 4 more Smart Citations
“…Similarly, Zhang et al observed similar properties in nitrogen doped benzoxazines (prepared as shown in Figure 9), finding that the sample with a lower nitrogen content had both a larger specific surface area and larger pore volumes than others [57]. Pores with higher surface areas have an increased ability to accumulate charges and transport ions, thus porosity measurements are crucial to understanding the electrochemical properties of benzoxazines [56,57]. Aside from porosity in general, mesopores can create ion transport channels within the carbon material (and grant ions entry to the electrode), thus highly mesoporous benzoxazines are highly suitable as electrodes [56].…”
Section: Electrochemical Propertiessupporting
confidence: 53%
“…Gao et al examined the electrochemical properties of carbon aerogels derived from nitrogen and sulfur co-doped polybenzoxazines and observed that the introduction of sulfur was key in preventing pore shrinkage, in addition to producing electrically active sites through redox reactions with the nitrogen and sulfur created pseudocapacitance (which was also observed in the nitrogen-only-doped benzoxazine) as a result of the enhanced porosity [56]. Similarly, Zhang et al observed similar properties in nitrogen doped benzoxazines (prepared as shown in Figure 9), finding that the sample with a lower nitrogen content had both a larger specific surface area and larger pore volumes than others [57]. Pores with higher surface areas have an increased ability to accumulate charges and transport ions, thus porosity measurements are crucial to understanding the electrochemical properties of benzoxazines [56,57].…”
Section: Electrochemical Propertiesmentioning
confidence: 69%
See 3 more Smart Citations